Do Voting Rights Notification Laws Increase Ex-Felon Turnout?. Issue 1 (January 2014) - Meredith, Marc; Morse, Michael
Previous research documents widespread confusion about who can and cannot vote among people who have come into contact with the criminal justice system. This research, and considerable activism drawing attention to the issue, has spurred a number of state legislatures to pass laws requiring the states to notify ex-felons about their voting rights. The purpose of this article is to better understand the policy processes that produce these notification laws and to assess whether the laws affect ex-felons' registration and turnout rates. Data on discharges from the correctional system and voter files are merged from three states that have recently passed notification laws: New Mexico, New York, and North Carolina. Our findings show little evidence of an increase in ex-felon registration or turnout after notification laws are implemented.